Association between periprocedural cerebral desaturation during transcatheter aortic valve implantation and postprocedural delirium: a prospective observational study - Hulya Yilmaz Ak; Baris Sandal; Yasemin Ozsahin; Ziya Salihoglu; Ahmet Yildiz; Esra Erturk Tekin; Mehmet Ali Yesiltas; Mustafa Yildiz; Kerem Erkalp (BMC Anesthesiology)
Abstract Background The aim of this study was to investigate whether the level of decrease in cerebral oxygen saturation during the valve placement phase of the transcatheter aortic valve implantation (TAVI) procedure under sedation has an effect on postoperative delirium (POD). Methods The study initially assessed 50 patients between the ages of 50 and 90 years with an indication for TAVI by the cardiac team. Regional cerebral oxygen saturation (rScO2) was measured using Near-infrared spectroscopy (NIRS) before the procedure (T1), during surgical field sterilization (T2), catheter placement (T3), wire manipulation (T4), valve placement (T5) and access site artery repair (T6). Confusion Assessment Method for The Intensive Care Unit (ICU-CAM) test was performed on intensive care unit and the presence of POD was questioned. Patients were divided into two groups as those without POD (Group 1) and those with POD (Group 2). Results The study was completed with 41 patients in total. While POD was present in 12 (29.3%) of the patients evaluated intensive care unit, POD was not observed in 29 (70.7%) patients. The rScO2 value measured at T5 was significantly lower in Group 2 compared to Group 1 (p < 0.001). Conclusions In our study, the rate of POD after TAVI was as high as 29.3%. Low rScO2 during valve placement was associated with delirium. Our findings indicate that NIRS devices could be a useful tool for assessing the risk of POD during the TAVI procedure; however, further research is needed to validate their routine clinical use.